MEG Node Degree Differences in Patients with Focal Epilepsy vs. Controls-Influence of Experimental Conditions - Vogel, Stephan; Kaltenhaeuser, Martin; Kim, Cora; Müller-Voggel, Nadia; Rössler, Karl; Dörfler, Arnd; Schwab, Stefan; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (Brain Sciences, 2021)
Drug-resistant epilepsy can be most limiting for patients, and surgery represents a viable therapy option. With the growing research on the human connectome and the evidence of epilepsy being a network disorder, connectivity analysis may be able to contribute to our understanding of epilepsy and may be potentially developed into clinical applications. In this magnetoencephalographic study, we determined the whole-brain node degree of connectivity levels in patients and controls. Resting-state activity was measured at five frequency bands in 15 healthy controls and 15 patients with focal epilepsy of different etiologies. The whole-brain all-to-all imaginary part of coherence in source space was then calculated. Node degree was determined and parcellated and was used for further statistical evaluation. In comparison to controls, we found a significantly higher overall node degree in patients with lesional and non-lesional epilepsy. Furthermore, we examined the conditions of high/reduced vigilance and open/closed eyes in controls, to analyze whether patient node degree levels can be achieved. We evaluated intraclass-correlation statistics (ICC) to evaluate the reproducibility. Connectivity and specifically node degree analysis could present new tools for one of the most common neurological diseases, with potential applications in epilepsy diagnostics.
CRIS-Team WoS Importer:2022-01-07